DOES A PLAYING COMPLEX INSTRUMENT BOOST COGNITIVE PERFORMANCE IN STUDENTS - Sonali (International Journal of Multidisciplinary Research and Studies, 2021)
There is no doubt that music has always played an important part in the development of human civilization, and that it is also an essential component of each and every community on the face of the globe. Making music has been one of the most essential activities that humans have participated in ever from the earliest times. There is no official record of early music because it was not passed down from generation to generation; however, flutes carved from bones have been recovered, which suggests that there was a musical presence in early society (O'Donnell 1999). This is due to the fact that early music was not passed down from generation to generation. It is common knowledge that the simple act of listening to music can cause changes in a person's state of mind, behaviour, and the easily measurable physiological processes of the body, such as the rate at which a person breathes, the pace at which a person's heart beats, and the blood pressure. These changes can be positive or negative depending on the type of music that is being listened to. (O'Donnell 1999).